2017
DOI: 10.1002/anie.201711098
|View full text |Cite
|
Sign up to set email alerts
|

Confined Carbon Mediating Dehydroaromatization of Methane over Mo/ZSM‐5

Abstract: Non‐oxidative dehydroaromatization of methane (MDA) is a promising catalytic process for direct valorization of natural gas to liquid hydrocarbons. The application of this reaction in practical technology is hindered by a lack of understanding about the mechanism and nature of the active sites in benchmark zeolite‐based Mo/ZSM‐5 catalysts, which precludes the solution of problems such as rapid catalyst deactivation. By applying spectroscopy and microscopy, it is shown that the active centers in Mo/ZSM‐5 are pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
183
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(199 citation statements)
references
References 39 publications
10
183
0
Order By: Relevance
“…These results are in agreement with Kosinov et al . who proposed that the conversion of methane to benzene might take place in a monofunctional manner on Mo carbides in the zeolite micropores, or mediated by carbonaceous species . Such mechanisms open the possibility to optimise active MDA catalysts based on non‐acidic zeolites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in agreement with Kosinov et al . who proposed that the conversion of methane to benzene might take place in a monofunctional manner on Mo carbides in the zeolite micropores, or mediated by carbonaceous species . Such mechanisms open the possibility to optimise active MDA catalysts based on non‐acidic zeolites.…”
Section: Discussionmentioning
confidence: 99%
“…[20] The same group has recently highlighted the involvement of confined carbon in the reaction mechanism instead. [21,22] Our previous synchrotron-based operando studies on Mo/H-ZSM-5 evidenced the relevance of Mo speciation in MDA product distribution. X-ray emission showed the selectivity to different hydrocarbon products to be dependent on Mo structure (i. e. partially carburised species were observed during the induction period when light hydrocarbons were produced, whereas fully carburised sites were selective to aromatics).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Mo/H-ZSM-5 ( Figure 1aii) showed anew band at 970 cm À1 as compared to MoO 3 and H-ZSM-5 physical mixture (Figure 1ai)a nd 973 Ka ir-treated H-ZSM-5 (Figure 1aiii). [3,12,20,21] Thei nduction (carburization) period and initial increase and subsequent reduction in aromatic formation rates with TOS( Figure 1e)i ss uggestive of ab ifunctional catalytic mechanism wherein CÀHb onds in CH 4 are activated on MoC x clusters formed during carburization to form C 2 H x species which subsequently undergo oligomerization/hydrogen transfer on residual Brønsted acid sites within zeolite channels to form aromatics.P revious reports showed that unsupported molybdenum carbide catalyzed CH 4 and C 2 H 6 conversion into C 2 products and ethylene,r espectively,b ut did not yield aromatics,w hereas MoC x /H-ZSM-5 catalyzed C 2 H 6 conversion into benzene,s uggesting that both carbidic MoC x sites and residual Brønsted acid sites are involved in CH 4 DHA. [3,12,20,21] Thei nduction (carburization) period and initial increase and subsequent reduction in aromatic formation rates with TOS( Figure 1e)i ss uggestive of ab ifunctional catalytic mechanism wherein CÀHb onds in CH 4 are activated on MoC x clusters formed during carburization to form C 2 H x species which subsequently undergo oligomerization/hydrogen transfer on residual Brønsted acid sites within zeolite channels to form aromatics.P revious reports showed that unsupported molybdenum carbide catalyzed CH 4 and C 2 H 6 conversion into C 2 products and ethylene,r espectively,b ut did not yield aromatics,w hereas MoC x /H-ZSM-5 catalyzed C 2 H 6 conversion into benzene,s uggesting that both carbidic MoC x sites and residual Brønsted acid sites are involved in CH 4 DHA.…”
mentioning
confidence: 97%
“…[3][4][5][6][7][8][9] Although the stoichiometry and coordination of MoC x clusters is still atopic of debate,the proficiency and reduced nature of active Mo-centers is no longer debated. [8,[10][11][12][13][14] Four noteworthy recent publications examine evolution and speciation of MoC x species in CH 4 DHA, [10,12,15,16] however, we make no effort to probe identity of MoC x species in this study and instead report in situ absorptive-hydrogen removal as as trategy to overcome thermodynamic limitations that limit single-pass conversion in CH 4 DHA to about 10 %. Arecent report proposes that addition of Zr metal as ah ydrogen absorber to MoO x /H-ZSM-5 formulations leads to increased CH 4 conversion and aromatic yields.…”
mentioning
confidence: 99%